Improving Conceptual Knowledge of the Italian Writing System in Kindergarten: A Cluster Randomized Trial - Pinto, Giuliana; Bigozzi, Lucia; Tarchi, Christian; Camilloni, Monica (Frontiers in Psychology, 2018)
This study assessed the efficacy of PASSI (Promoting the Achievement of Sound-Sign Integration), an intervention to improve children’s conceptual knowledge of the Italian writing system in kindergarten, which is an emergent literacy predictor of reading and spelling acquisition focused on letter-speech sound integration. PASSI implements an embedded-explicit approach in which teachers target specific subskills (reflection on the graphic, symbolic and phonological aspect of written signs) and emphasize children’s contextualized interactions with oral and written language. One hundred fifty-nine Italian children participated in this study. Six teachers (and their three respective classes) were randomly assigned to the experimental group, and six teachers were assigned to the control group. All children were tested on the invented spelling of words and numbers, knowledge of the alphabet, orthographic awareness, and drawing twice, before and after the intervention. Children’s visual-motor integration skills were also assessed as a control variable. The data were analyzed through the complex samples general linear model approach. The results confirmed the efficacy of PASSI in promoting children’s conceptual knowledge of the writing system and related emergent literacy skills. Theoretical and educational implications of the results are presented and discussed.